Pharmacokinetic drug interactions between opioid agonist therapy and antiretroviral medications: implications and management for clinical practice. - Bruce, R Douglas; Altice, Frederick L; Gourevitch, Marc N; Friedland, Gerald H (Journal of acquired immune deficiency syndromes (1999), 2006)
Opioid dependence and HIV/AIDS are 2 of the most serious yet treatable diseases worldwide. Global access to opioid agonist therapy and HIV treatment is expanding but when concurrently used, problematic pharmacokinetic drug interactions can occur.
Keywords: Acquired Immunodeficiency Syndrome; Analgesics, Opioid; Anti-HIV Agents; Buprenorphine; Drug Interactions; HIV Infections; Humans; Methadone